Exposure to non-endemic arboviruses (alphaviruses) in Costa Rica assessed from human samples collected in areas with contrasting levels of dengue endemicity - Valles-Morera, Andrea; Murillo, Tatiana; Lizano-Bolaños, Jose; Gutierrez-Roche, Sergio; Alvarado, Margarita; Alfaro-Alvarado, Jonathan; Calvo-Salas, Gerardo Andrés; Prado-Hidalgo, Grace; Ortega, Johis; Corrales-Aguilar, Eugenia (Frontiers in Public Health, 2025)
Arboviruses represent a global public health challenge. The lack of diagnostic protocols and the presence of asymptomatic infections complicate confirmatory diagnostics. Alphaviruses, such as the equine encephalitis viruses, can cause severe outbreaks and are usually misdiagnosed as dengue. Thus, evidence for their circulation was assessed here. Plaque reduction neutralization test (PRNT) was used to compare sera collected during 2022–2023 from an area with high dengue endemicity (Hone Creek) with another with low endemicity (Great Metropolitan Area, GMA) to elucidate the putative alphavirus circulation and determine whether there were differences between the two areas. The screening results of PRNT50% against the Venezuelan equine encephalitis virus (VEEV) and the Eastern equine encephalitis virus showed that 20.5% of sera collected from Hone Creek were positive for VEEV, with 15.4% (n = 40) showing real neutralizing titers. In the GMA, only 0.8% tested positive for VEEV during the screening, with only 0.3% (n = 1) showing a true neutralizing titer. No sample was positive for the Eastern equine encephalitis virus or Mayaro (MAYV) and one serum sample from Hone Creek was chikungunya positive. This study underscores the global health challenge posed by arboviruses with their similar clinical presentation and antibody cross-reactivity, particularly in tropical regions where flaviviruses and alphaviruses prevail and co-circulate. The comparison of PRNT results between high and low dengue-endemic areas in Costa Rica shed light on the potential circulation of the VEEV and the fact that there is no circulation of Eastern equine encephalitis virus or Mayaro yet. These findings indicate a higher prevalence of VEEV in the high-endemic area, emphasizing the importance of targeted surveillance, control measures, and better diagnostics.